Aligning resettlement planning and livelihood restoration with social impact assessment: a practitioner perspective. Issue 1 (2nd January 2017) - Rowan, Marielle
Abstract: Large infrastructure projects involving land acquisition frequently require resettlement planning to be undertaken during the environmental and social impact assessment. However, resettlement planning needs more design detail than is usually available during a social impact assessment (SIA). Resettlement planning is best scheduled after an SIA required for environmental permitting. Timing and duration also influence the effectiveness of livelihood restoration, in particular in-kind support to build social resilience. Cash compensation, as a one-time payment, is not constructive for long term livelihood restoration. Using examples from international infrastructure projects, this paper reviews where SIA and resettlement planning intersect in the project cycle and considers the implications for the timing of livelihood restoration measures.